CHANGES IN THE SYSTEM OF VOCATIONAL AND TECHNICAL EDUCATION IN UZBEKISTAN IN 1960-1980 (Scientific journal of the Fergana State University, 2024)
The article tried to highlight the changes that occurred in the system of vocational education of Uzbekistan in the 60-80s of the twentieth century, the laws and regulations of the Soviet government in the field of education, problems in their implementation, achievements in the field of vocational education and problems emerged in this area. Also in this article, the author examines the basis of new historical sources, archival materials, memoirs, letters, materials of the modern press, narrative sources, the dedicated work of workers in the education system of Uzbekistan during the period under review, an objective assessment of the positive and negative aspects that occurred in the education system, the restoration of historical truth , encouraging youth. Loyalty to the Motherland, education in the spirit of endless respect for predecessors, self-awareness, helps to draw appropriate conclusions from the lessons of the past.